Teachers’ Pedagogical Competence in Supporting Inclusive Students: A Case Study of Grade V at SDN Cikampek Utara III - Muhamad Hafid Fahri; Tarpan Suparman; Andes Safarandes Asmara; Depi Prihamdani; Anggy Giri Prawiyogi (Journal of General Education and Humanities, 2026)
Inclusive education requires teachers to adapt instruction to diverse student characteristics and learning needs. However, how student identification, instructional adaptation, assessment, and follow-up operate as an integrated pedagogical process remains underexplored. This study analyzed teachers’ pedagogical competence in supporting inclusive students in Grade V at State Elementary School Cikampek Utara III. A qualitative case study involved two purposively selected Grade V homeroom teachers. Data were collected through classroom observations, semi-structured interviews, and documentation and analyzed using the Miles and Huberman model. The study established data trustworthiness through triangulation. The findings showed that teachers identified students’ abilities, needs, participation, and learning progress and used this information to adapt methods, media, tasks, learning time, and individual support. Teachers used assessment to monitor development and determine remedial activities, enrichment, and further instructional adjustments. Pedagogical competence was reflected in responsive instructional practices through a cyclical process of student identification, instructional adaptation, assessment, and follow-up action. Given the limited sample and single-school setting, the findings are context-specific. The study highlights the need for continuous professional development in inclusive pedagogy, differentiated assessment, collaborative planning, and structured teacher reflection.